Adhesion of cast metal alloy and lithium disilicate copings luted to different core build-up materials with self-adhesive resin cement. Issue 3 (1st February 2017) - Al-Dwairi, Ziad Nawaf; Aleisa, Khalil; Al-Beshr, Abdulhameed; Al-Habdan, Yazeed; Al-Harbi, Faisal; Al-Haj Husain, Nadin; Özcan, Mutlu
Abstract: This study evaluated the shear bond strength of two coping materials (non-nickel chrome-based cast alloy and lithium disilicate ceramic (IPS Empress) to four different core foundation materials (resin composite, cast metal alloy, lithium disilicate, and dentin), luted with adhesive resin cement (RelyX Unicem). Specimens ( N  = 56) were fabricated and divided into eight groups ( n  = 7 per group). Each coping material was luted with self-adhesive resin cement (RelyX Unicem) to the core materials. Bond strength was measured in a Universal Testing Machine (0.5 mm/min). Data were statistically analyzed using a two-way analysis of variance (ANOVA) and Tukey's HSD tests (alpha = 0.05). Both core ( p  = 0.000) and coping material type ( p  = 0.000) significantly affected the mean bond strength (MPa) values. Interaction terms were also significant ( p  = 0.001). The highest bond strength results were obtained when lithium disilicate was bonded to lithium disilicate (21.48) with the resin cement tested. Lithium disilicate in general presented the highest bond results when bonded to all core materials tested (16.55–21.38) except dentin (3.56). Both cast alloy (2.9) and lithium disilicate (3.56) presented the lowest bond results on dentin followed by cast-alloy-cast alloy combination (3.82).